PP.18.21: ESTIMATION OF LOCAL VASCULAR DAMAGE ASSESSED BY CAROTID-RADIAL PULSE WAVE VELOCITY IN PATIENTS TREATED WITH CHEST RADIOTHERAPY. (June 2015) - Stucchi, M.; Vallerio, P.; Moreo, A.; Musca, F.; Colombo, G.; Sormani, P.; Maloberti, A.; Marullo, G.; Ribecca, D.; Sarno, M.; Mancia, G.; Palazzi, M.; et al.
Abstract : Objective: Radiotherapy (RT) of thoracic cancers exposes to late radiation induced complications, strengthened from pre-existing cardiovascular risk factors. The heart post-RT damage is a well known phenomenon and conformational RT has allowed its drastic reduction. However, prolonged life expectancy of cancer patients underlines the need to evaluate cardio-vascular risk for many years after therapy, also in attempt to prevent the increase cardiovascular mortality that it has been recently proposed in radio-treated subjects. An arterial structural or functional damage induced by RT might be one of mechanisms for increased atherosclerotic process in these subjects. Aim of our study was to evaluate arterial function by means of PWV and Aix in subjects treated by chest radiotherapy. Design and method: We enrolled 42 patients treated with radiotherapy 15 years ago for Mammary Cancer. We assessed traditional risk factors, atherosclerotic organ damage (Carotid Ultrasound) and functional arteries evaluation with carotid-radial PWV (Complior) and AIx (Sphygmocor). We divided patients in R (N = 26) (therapy on right mammary gland), and L (N = 18) (left mammary gland). Results: None of patients had story of cardiac artery disease. R and L had similar ages (70 ± 8vs68 ± 8 yrs, means+SD), BSA (1.68 ± 0.16vs1.7 ± 0.12 m2), distribution of hypercholesterolemia (40vs39%) and active smoking (8vs7%). R had higher prevalence of hypertension (60vs57%), instead L of diabetes (17vs12%). IMT was more frequently increased (>0.9 mm) in R than in L (38vs33%). R had a significantly increased cr-PWV on right arm compared with left arm (9.9 ± 1.4vs8.9 ± 1.2, p < 0.05); L had a significantly increased cr-PWV (9.5 ± 1.5vs9 ± 1.3, p < 0.05) and AIx on left arm (32.1 ± 7.6vs28.3 ± 6.8, p < 0.05). In both groups no significant differences were found on central blood pressure estimation between right and left arm. No correlations were found with hormone-therapy or chemotherapy. Conclusions: Our preliminary data suggest that arteries function reflects a possible local damage due to RT. This specific and local increased in arterial stiffness might be one of mechanisms under the increase atherosclerotic phenomenon and subsequent pathologies in RT patients. It could be useful to estimate the global cardio-vascular damage in patients subjected to chest radiotherapy and to access a complete cardio-vascular risk stratification in order to plan an optimized cardio-preventive strategy.